2018
DOI: 10.1055/s-0043-123765
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and complications of submucosal tunneling endoscopic resection for upper gastrointestinal submucosal tumors and exploration for influencing factors

Abstract: STER appeared to be an extremely effective technique for removing upper GI SMTs originating from the muscularis propria layer. In addition, the very low rate of complications also shows the safety of this technique. Tumor size, infiltration depth, and location may influence the complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Gas-related and inflammation-related complications were the major complications for STER according to previous study, such as subcutaneous emphysema, pneumothorax, and pleural effusion [19]. While in our study, only 1 patient developed moderate fever and mucosal nonunion.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…Gas-related and inflammation-related complications were the major complications for STER according to previous study, such as subcutaneous emphysema, pneumothorax, and pleural effusion [19]. While in our study, only 1 patient developed moderate fever and mucosal nonunion.…”
Section: Discussionmentioning
confidence: 38%
“…Management of SMTs originating from the MP layers remains a controversial topic [19]. In the past, open or thoracoscopic surgery was performed to remove SMTs, even without accurate orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The STER-related complication rates mainly range from 5% to 25% with no reported deaths, and most of the complications reported are mild[14], which is in accordance with our results. A meta-analysis involving 12 studies including 397 patients and 430 lesions showed that the pooled complication rate of STER for GI SMTs was 21.5% (95%CI: 13.2-33.1%)[25]. Gas-related complications are regarded as the most common complication related to STER[28,35,45,46,48].…”
Section: Discussionmentioning
confidence: 99%
“…5,[31][32][33] A meta-analysis involving 12 studies including 397 patients and 430 lesions showed that the pooled complication rate of STER is 21.5% (95% confidence interval [CI], 13.2-33.1). 34 Gas related events are most com- monly observed during STER. In a systematic review, the pooled prevalence of gas-related events was 14.8% (95% CI, 10.5-20.5) for subcutaneous emphysema and pneumomediastinum, 6.1% (95% CI, 4.0-9.0) for pneumothorax, and 6.8% (95% CI, 4.7-9.6) for pneumoperitoneum.…”
Section: Stermentioning
confidence: 99%
“…35 Gas related complications occur more frequently in esophageal tumors and mucosal injuries were seen in cardia tumor. 33,34 The main reason for differences in the complications between esophageal and cardia tumor is the absence of serosa in esophagus and a thicker muscularis propria (MP) in cardia which reduces the likelihood of gas related complication. In addition, the complex anatomy of cardia increases the risk of mucosal injury.…”
Section: Stermentioning
confidence: 99%